2021
DOI: 10.1007/s00204-021-03199-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-VX exposure treatment of rats with engineered phosphotriesterases

Abstract: The biologically stable and highly toxic organophosphorus nerve agent (OP) VX poses a major health threat. Standard medical therapy, consisting of reactivators and competitive muscarinic receptor antagonists, is insufficient. Recently, two engineered mutants of the Brevundimonas diminuta phosphotriesterase (PTE) with enhanced catalytic efficiency (kcat/KM = 21 to 38 × 106 M−1 min−1) towards VX and a preferential hydrolysis of the more toxic P(−) enantiomer were described: PTE-C23(R152E)-PAS(100)-10-2-C3(I106A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, we were able to identify some critical amino acid positions for expression yield and folding efficiency or thermal stability (306, 303, 233, 259 and 260, 262, 267, 257). This knowledge may prove useful during future biopharmaceutical development as a catalytic bioscavenger for the treatment of acute intoxications by nerve agents 15 as well as OP pesticides, for example when combined with other promising mutants to build a heterodimeric PTE with a broader substrate profile. 56 ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were able to identify some critical amino acid positions for expression yield and folding efficiency or thermal stability (306, 303, 233, 259 and 260, 262, 267, 257). This knowledge may prove useful during future biopharmaceutical development as a catalytic bioscavenger for the treatment of acute intoxications by nerve agents 15 as well as OP pesticides, for example when combined with other promising mutants to build a heterodimeric PTE with a broader substrate profile. 56 ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 99%
“…13 Moreover, we found that this mutant exhibits high hydrolytic activities toward several other nerve agents, including GD, 14 and a PASylated version of this BdPTE variant with an extended plasma half-life showed promising results in vivo in a rat treatment study after VX poisoning. 15 To better understand the role of some enzyme active site residues for the phosphorothioester bond cleavage in VX and related OP substrates, we set out to examine the crystal structure of this mutant BdPTE and, based on this information, we constructed 30 new mutants and analyzed their hydrolytic activities toward a representative set of four nerve agents: VX, VR, GB, and GF (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The µLC-ESI MS/HR MS (PIS) method (method A) for biomarker detection was applied to heparin plasma obtained from an in vivo study with male Wistar rats. Details on the scope, conditions and results of the study are described by Stigler et al (Stigler et al 2022 ). In brief, male Wistar rats were anaesthetized under continuous surveillance of anaesthesia depth and exposed to VX subcutaneously (s.c.) using a dose of 25 µg/kg (approximately 2 × LD 50 for rats i.m.)…”
Section: Methodsmentioning
confidence: 99%
“…P02770) in plasma is similar to that in humans (40 mg/mL) (Metz und Schütze 1975 ) and RSA also contains a reactive Tyr 411 and a Cys 34 residue exhibiting a free thiol group (Chen et al 2013 ) as well as a LeuProCys 448 sequence as an analogue to the human MetProCys 448 (Kranawetvogl et al 2018a ). Accordingly, we developed and validated a µLC-ESI MS/HR MS method for the qualitative detection of adducted biomarkers and applied it to an in vivo study of VX-exposed rats (Stigler et al 2022 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Since 2018, in the toxicological literature, the following lines of investigation can be identified, which are reflected by key contributions to Archives of Toxicology. Clinical reports (Novichok) and improvement of therapy of intoxications by organophosphorus compounds (Hulse et al 2019 ; Steindl et al 2021 ; Vale et al 2018 ; Worek et al 2020 ; Zandona et al 2020 , 2021 ): a special focus is development of novel antidotes, e.g., novel oximes (Machamer et al 2020 ; Zandona et al 2020 , 2021 ) or engineered phoshotriesterases (Stigler et al 2021 ). Given the world-wide incidents attributed to chemical weapons, such as Novichok agents, intensive-care clinicians should know how to rapidly recognize symptoms of acute poisoning and to administer life-saving antidotal therapy, when indicated (Chai et al 2018 ).…”
mentioning
confidence: 99%